Comprehensive review on pharmacological potential of Illicium verum, Chinese herb - Sonia Singh; Riya Verma (Elsevier, 2024)
Introduction: Star anise is also known as Illicium verum Hook. f. is a powerful plant that plays a significant role in traditional Chinese and Asian medicine. The perfume of the fruit is there, and it has a spicy and slightly sweet flavor. It has several polyphenolic and flavonoid compounds with antibacterial, antifungal, anti-oxidant, and anti-inflammatory activities. Materials and methods: The content for manuscript were collected from Scopus, Google Scholar, PubMed, and Research Gate using the terms ''star anise,'' ''traditional Chinese medicine,'' ''anise,'' and ''pharmacological activities". The information has been gathered till 2023.The manuscript has included the patent concerned to the Illicium verum. Result and conclusion: Anethole, found in the Chinese star anise essential oil, has been demonstrated to possess several functional qualities, including anti-oxidant, antibacterial, and anticancer effects. Most substances found in anise seed oil are as follows: anethol, eugenol, anisaldehyde, coumarins, terpene hydrocarbons, umbelliferon, and methyl chavicol. The pharmacological effects include antibacterial, antifungal, anti-oxidant, and anti-inflammatory activities.